Influência de produtos e procedimentos estéticos na aquisição de imagens termográficas em região de face - Ferreira, Jose Eraldo Viana (2023)
Skin temperature variations demonstrated in healthy people have multifactorial origins, being attributable both to external factors, such as the precision characteristics of the IRT equipment, environment and measurement technique, and to internal factors, such as the physiological variability of blood flow. This study aimed to evaluate whether the use of topical cosmetic products and the performance of an injectable aesthetic procedure before the thermographic examination can change the skin temperature in the facial region. An experimental study with a quantitative and analytical approach was carried out. The study was carried out at the Department of Dentistry at the State University of Paraíba. The images were collected at the Infrared Thermography Diagnostic Laboratory. The sample consisted of 76 participants previously selected taking into account the eligibility criteria. Three topical products were used (2 sunscreens and a facial foundation) and an infiltrative product (BTX-A). The topical product was applied to the participant's entire face, previously cleansed. The application of botulinum toxin was carried out in accordance with the manufacturer, the product was diluted in sterile serum in the following proportion: 2mls of serum for 500iu of toxin. A 0.5ml BD syringe and 6mm 31G needle were used. For the Thermography examination, the patient was taken to the examination room. The room was airconditioned, with temperature (between 21ºC) and relative humidity (less than 60%) controlled by a thermo-hygrometer. The images were obtained using the FLIR T650s Thermal Camera (FLIR, USA), with integrated visible light CCD camera, spectrum detector between 7.5 and 13μm, temperature range from -40ºC to 150ºC, high spatial resolution 640x480. A total of 732 images were obtained and 2,532 ROIs were analyzed. Thermal camera images were analyzed using FLIR Thermal Studio software version 1.9.70. Data were evaluated using Jamovi 2.3 software (Computer Software Inc., Sydney, Australia). To check normality, the Shapiro-Wilk test was used. The Levene and Mauchly tests were used to evaluate the homogeneity of variances. Mixed ANOVA, with Tukey's post hoc test, was used to determine interactions between factors in the dependent variable mean temperature. For independent samples, involving three groups, One-Way ANOVA was used, with Tukey's post hoc test. The significance level was set at 5%, considering p < 0.05. The results showed temperature variation in relation to all analyzed products, in the frontal and side views the values varied from 0.6ºC to 1.7ºC, at the moment right after the greatest temperature variations were found, and male individuals higher values when compared to females. After applying topical cosmetic products (anti-aging sunscreen, anti-oil sunscreen and easy foundation), temperature variations were observed on the face, the anti-oil sunscreen raised the temperature of the region while the anti-aging sunscreen and foundation decreased the temperature. temperature of the analyzed region. Regarding BTX-A, it was observed that it raised the temperature of the applied region even 5 days after application. Key words: botulinum toxins type a; skin; cosmetics; thermography; face.